Estimation of damage severity using sparse static measurement. Issue 2 (17th February 2017) - Grandić, Ivana Štimac; Grandić, Davor
Abstract: A new structural damage estimation procedure using grey relation coefficient and curvature of displacement influence line in beams using sparse measurement is proposed in this paper. The method is based on static structural response which can be obtained using single sensor. determination of damage location as well as determination of corresponding damage severity can be easily calculated with simple arithmetic operations, which is the main advantage of the proposed method. Conducted numerical simulation for different damage scenarios and various measurement sparseness and experimental validation confirm the effectiveness of proposed damage severity estimation procedure.